Effective enzymatic in situ saccharification of bamboo shoot shell pretreated by dilute alkalic salts sodium hypochlorite/sodium sulfide pretreatment under the autoclave system. (October 2017) - Chong, Gang-Gang; He, Yu-Cai; Liu, Qiu-Xiang; Kou, Xiao-Qin; Huang, Xiao-Jun; Di, Jun-Hua; Ma, Cui-Luan
Graphical abstract: Highlights: Combined NaClO/Na2 S pretreatment under autoclave was firstly used to pretreat BSS. Dilute alkalic salt (0.6% NaClO, 10% sulfidity) was successfully to pretreat BSS. Saccharification of 20–50 g/L BSS were obtained at 56.1–69.4% in alkalic salt media. Ethanol fermentability of BSS-hydrolysates was demonstrated in alkalic salt media. Abstract: In this study, dilute alkali salts (0.6% NaClO, 0.067% Na2 S) pretreatment at 10% sulfidity under the autoclave system at 120 °C for 40 min was used for pretreating bamboo shoot shell (BSS). Furthermore, FT-IR, XRD and SEM were employed to characterize the changes in the cellulose structural characteristics (porosity, morphology, and crystallinity) of the pretreated BSS solid residue. After 72 h, the reducing sugars and glucose from the enzymatic in situ hydrolysis of 50 g/L pretreated BSS in dilute NaClO/Na2 S media could be obtained at 31.11 and 20.32 g/L, respectively. Finally, the obtained BSS-hydrolysates containing alkalic salt NaClO/Na2 S resulted in slightly negative effects on the ethanol production. Glucose in BSS-hydrolysates was fermented from 20.0 to 0.17 g/L within 48 h, and an ethanol yield of 0.41 g/g glucose, which represents 80.1% of the theoretical yield, was obtained. This study provided an effective strategy for potential utilization of BSS.